Children's exposure to food advertising: the impact of statutory restrictions. (30th October 2017) - Whalen, Rosa; Harrold, Joanne; Child, Simon; Halford, Jason; Boyland, Emma
Abstract: Evidence demonstrating links between exposure to unhealthy food marketing, poor eating behaviours and paediatric obesity has led to calls for regulatory change in many countries, including the UK. However no official monitoring system exists to inform international debate on food advertising policy. This study systematically explores food advertising on UK television in 2010 (post-regulation) and compare this to 2008 (mid-regulation) to assess if food adverts improved in nutritional quality after implementation of regulations. Television was recorded between 6 a.m. and 10 p.m. for one weekday and one weekend day during 6 months of 2010 across 13 commercial television channels popular with children. These data were directly compared with previously published data for 2008. Food and beverages were the third most frequently advertised product type (11.9% of all ads), a decrease of 0.9% from 2008 (12.8%). Non-core food commercials decreased (down 2.2–53.8%) and core food advertising increased (up 0.5–18.6%). Fast food items were the third most frequently advertised food product (15.4%, up 3.5% from 2008). During peak children's viewing times, 17.0% of all commercials were for food, an increase of 4.7% from non-peak children's viewing times and fewer core (−0.9%) and more non-core (+0.5%) foods were advertised at these times. Despite statutory regulation, frequency and balance of food commercials (core, non-core and miscellaneous) remained relatively static over the 2 years. Children are still exposed to high amounts of unhealthy food advertising on television. Continued monitoring of television food advertising remains crucial and policymakers should examine the comparative efficacy of other restrictions.